The Pragmatic Digital Believer: Why Gen Z Prioritizes Value over Religious Identity in the Shopee Ecosystem - Zainiyatul Musallimah (Journal of Digital Economic Studies, 2026)
The rapid digitization of the Islamic economy has birthed a complex tension between religious idealism and market pragmatism. This study investigates the hierarchy of purchase determinants among Generation Z Muslims in Surabaya, specifically within the Shopee fashion ecosystem. Employing a quantitative explanatory design with 100 respondents, this research utilizes multiple linear regression to analyze the contestation between utilitarian variables (Product Quality and Price) and theological variables (Halal Awareness). The findings reveal a striking paradox: while the model collectively predicts 88.4% of purchase decisions, Halal Awareness fails to demonstrate statistical significance (p > 0.05). Conversely, Product Quality and Price emerge as absolute determinants with high levels of significance. These results challenge the prevailing assumption of blind faith-based loyalty, suggesting a paradigm shift towards “Pragmatic-Religious Consumption.” Generation Z operates as rational economic actors who prioritize visual aesthetics and cost efficiency over formal religious labeling in the context of fashion. Consequently, the industry must pivot from symbolic religious marketing to substantive value creation to capture this critical demographic.